2020
DOI: 10.1093/rheumatology/keaa796
|View full text |Cite
|
Sign up to set email alerts
|

De novo lupus nephritis during treatment with belimumab

Abstract: Objective In light of reports of de novo LN during belimumab (BLM) treatment, we sought to determine its frequency and contributing or protective factors in a real-life setting. Methods Patients with SLE who received BLM between 2011 and 2017 at five European academic practices were enrolled (n = 95) and followed longitudinally for a median time of 13.1 months [interquartile range (IQR): 6.0–34.7]; 52.6% were anti-dsDNA posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…However, early identification of patients at risk for subsequent flares upon commencement of belimumab treatment remains a challenge, leaving an area of uncertainty during the critical stages of early follow-up. This need was recently exemplified in a report of de novo lupus nephritis cases after initiation of belimumab therapy ( 22 ).…”
Section: Introductionmentioning
confidence: 96%
“…However, early identification of patients at risk for subsequent flares upon commencement of belimumab treatment remains a challenge, leaving an area of uncertainty during the critical stages of early follow-up. This need was recently exemplified in a report of de novo lupus nephritis cases after initiation of belimumab therapy ( 22 ).…”
Section: Introductionmentioning
confidence: 96%
“…(3 de-novo LN out of 66 patients without prior LN; and 2 LN flares among 29 patients with known LN). 102 …”
Section: The Product Of Interestmentioning
confidence: 99%
“…treated with BEL Riancho-Zarrabeitia L 106 2020 retrospective analysis 1/11 HCQ (all) MMF, AZA, CYC, LEF (several) 1 case of de novo LN in a cohort of 11 SLE pts. treated with BEL for musculoskeletal and/or cutaneous manifestations Hassan S 107 2020 prospective observational study 2/14 SoC study with secondary non-responders to RTX in SLE, details see Table 4 1 patient relapsed with LN class III during BEL treatment, another developed de novo LN class V; both were then treated with CYC Parodis I 102 2020 prospective observational study 6/66 de novo 2/29 flare SoC 6 out of 66 SLE pts. with no prior history of LN developed biopsy-proven LN during BEL treatment (after a median of 7.4 m); 2 out of 66 control pts.…”
Section: The Product Of Interestmentioning
confidence: 99%
“…Of notice, both these patients improved immediately by withdrawal of belimumab and before the initiation of standard therapy. Furthermore, a retrospective study recently reported that introducing belimumab into a standard treatment regimen of patients with lupus without nephritis resulted in development of lupus nephritis with an increased frequency compared to a control group of patients with lupus (hazard ratio, HR: 10.7; p = 0.012) (27). The authors proposed that concomitant treatment with antimalarials was protective over this "nephritogenic" potential of belimumab (HR: 0.2; p = 0.046).…”
Section: Blocking Blys In Lupus Nephritismentioning
confidence: 99%